Project management of the Ayacucho Airport Repaving - Chavez Plasencia, Rony (2020)
The construction field is always strategic in the development of a country. In recent years, due to the economic recession and it has been losing good management practices. In this context, the need for implementing new management processes has become essential. This research explains the implementation of a Balanced Scorecard, project management, and Due Diligence (related to ISO 37001) to improve the administrative results of the construction Project “Repavimetación del Aeropuerto de Ayacucho”.